Long-term evaluation in BALBc mice of a triple mutant of Mycobacterium bovis and the Bacillus Calmette-Guérin as potential vaccines against bovine tuberculosis - Blanco, Federico Carlos; Marini, María Rocío; Klepp, Laura Ines; Vazquez, Cristina Lourdes; Garcia, Elizabeth Andrea; Bigi, María Mercedes; Canal, Ana María; Bigi, Fabiana (Elsevier, 2025)
There is currently no commercial vaccine available against bovine tuberculosis (bTB). Mycobacterium bovis is the primary causative agent of bTB and is closely related to Mycobacterium tuberculosis, the pathogen responsible for human TB. Despite their limitations, mouse models are invaluable in early vaccine development due to their genetic diversity, cost-effectiveness, and the availability of research tools. Researchers have tested many TB vaccines in mice, although few specifically target bTB. In this study, we developed a mutant strain of M. bovis lacking the esxA, esxB genes and the virulence gene fbpA to evaluate its long-term protective efficacy in BALB/c mice. We also analysed local immune responses and compared the results with those of BCG vaccination. Both BCG and the triple mutant strain Mb303ΔesxABΔfbpA demonstrated protection in BALB/c mice against M. bovis challenge, as evidenced by reduced bacterial lung loads. A histopathological analysis revealed the absence of ZN+ bacteria in the lungs of M. bovis-challenged mice vaccinated with BCG. In addition, mice vaccinated with the triple mutant exhibited a higher profile of protective immune CD4 + T cells in the lungs than those vaccinated with BCG. Notably, there was a negative correlation between the bacterial loads in the lungs of mice and the T cell subpopulations CD4 +KLRG1-PD1 +CCR7 + and CD4 +KLRG1-CXCR3 + , indicating that these T cell phenotypes are potential markers of protection against bTB. These findings indicate that the Mb303ΔesxABΔfbpA strain provides long-term protection against bTB. Furthermore, the results reaffirm the potential of BCG as a vaccine against this disease.